Excitation selective thermal characteristics of Mg28Ge7.55−xGaxO32F15.04: Mn4+ and application in single/dual-mode optical thermometry. (September 2021) - Yang, Zhibin; Wang, Zhijun; Zheng, Mingjie; Wang, Xuejiao; Cui, Jia; Yao, Yao; Cao, Lingwei; Zhang, Mengya; Suo, Hao; Li, Panlai
Abstract: Currently, the transition metal ions Mn 4+ are fascinating for its potential in diverse luminescence application fields. Herein, a series of Mg28 Ge7.55−x Gax O32 F15.04 : Mn 4+ phosphors available for optical thermometry have been obtained by introducing Ga 3+ into Mg28 Ge7.55 O32 F15.04 : Mn 4+ . It is noteworthy that the phosphors show excitation selective thermal characteristics with temperature changing from 303 to 473 K, i.e., decreasing (270–340 nm/405–435 nm), essentially unchanged (356–378 nm), and increasing (445–500 nm), respectively. The emission intensity of anti-Stokes and Stokes peaks of Mg28 Ge6.35 Ga1.2 O32 F15.04 : Mn 4+ show inverse trends under the same excitation, which imply the application potential of the phosphor in single-mode optical thermometry. The relative sensitivity ( S r ) of the single-mode thermometer reached 0.68% K −1 . In addition, the Eu 2+ /Mn 4+ dual-mode optical thermometer has also been realized by taking advantage of the significantly different thermal quenching characteristics of Mg28 Ge6.35 Ga1.2 O32 F15.04 : Mn 4+ and Ba2 Mg(PO4 )2 : Eu 2+ under the same 365 nm excitation. The maximum S r value of Eu 2+ /Mn 4+ dual-mode thermometer was 1.38% K −1 . This work not only indicates Mg28 Ge6.35 Ga1.2 O32 F15.04 : Mn 4+ can be a promising candidate for optical thermometry, but also expands new horizons with the topological composite pathway toward rational designing and perfecting dual or even multi-mode thermometers. Highlights: Mn 4+ doped Mg28 Ge7.55 O32 F15.04 phosphors can show deep red emission. Eu 2+ /Mn 4+ dual-mode optical thermometry has been realized innovatively. The intensity of Mn 4+ can be improved based on the cation substitution strategy.